2021
DOI: 10.1111/echo.15238
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in mitral valve geometry after percutaneous valve repair with MitraClip XTR by three‐dimensional echocardiography

Abstract: Background: Mitral valve (MV) repair with MitraClip system is a safe treatment option for high-risk patients with significant mitral regurgitation (MR). We aimed to characterize, by three-dimensional echocardiography (3D-E), changes occurring in MV after implantation of third generation MitraClip XT R device, with specific reference to the underlying MR mechanism (functional vs degenerative, FMR vs DMR). Methods:We prospectively enrolled 59 patients, who underwent intra-procedural 3D-E before and after device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Previous studies evaluating short‐term effects of the MitraClip system on MV geometry demonstrated a significant reduction of the AP diameter and annular dimensions. 3 , 5 Our findings confirm these described effects in a saddle‐shaped 4D MV model. Notably, despite the more flexible scaffold, the PASCAL‐treated cohort demonstrated a comparable reduction of the AP diameter, annular circumference, and area of the MV.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies evaluating short‐term effects of the MitraClip system on MV geometry demonstrated a significant reduction of the AP diameter and annular dimensions. 3 , 5 Our findings confirm these described effects in a saddle‐shaped 4D MV model. Notably, despite the more flexible scaffold, the PASCAL‐treated cohort demonstrated a comparable reduction of the AP diameter, annular circumference, and area of the MV.…”
Section: Discussionsupporting
confidence: 87%
“… 3 Previous studies demonstrated that TEER using the MitraClip system (Abbott Vascular, Santa Clara, CA) significantly reduced annular dimensions throughout the cardiac cycle in both primary mitral regurgitation (PMR) and SMR, as quantified by 3‐dimensional (3D) echocardiography. 4 , 5 …”
mentioning
confidence: 99%
“…TEER can reduce the intensity of the symptoms of SMR and its prevalence because of the acute changes in mitral valve geometry as follows; improved coaptation area and mitral valve tethering, decreased anteroposterior diameter and area of the mitral annulus, and increased sphericity of the mitral annulus ( 45 50 ), all of which lead to a persistent reduction of the SMR and improvement of the functional status ( 45 , 46 ). Such acute changes following TEER seem to resist dynamic SMR derived from changes in the mitral valve geometry during exercise.…”
Section: Teer For Dynamic Smrmentioning
confidence: 99%